Structural and Phylogenetic Studies with MjTX-I Reveal a Multi-Oligomeric Toxin - a Novel Feature in Lys49-PLA2s Protein Class - Salvador, Guilherme H. M. [UNESP]; Fernandes, Carlos A. H. [UNESP]; Magro, Angelo J. [UNESP]; Marchi-Salvador, Daniela P. [UNESP]; Cavalcante, Walter L. G. [UNESP]; Fernandez, Roberto M. [UNESP]; Gallacci, Márcia [UNESP]; Soares, Andreimar M.; Oliveira, Cristiano L. P.; Fontes, Marcos R. M. [UNESP] (Public Library of Science (PLoS), 2013)
The mortality caused by snakebites is more damaging than many tropical diseases, such as dengue haemorrhagic fever, cholera, leishmaniasis, schistosomiasis and Chagas disease. For this reason, snakebite envenoming adversely affects health services of tropical and subtropical countries and is recognized as a neglected disease by the World Health Organization. One of the main components of snake venoms is the Lys49-phospholipases A2, which is catalytically inactive but possesses other toxic and pharmacological activities. Preliminary studies with MjTX-I from Bothrops moojeni snake venom revealed intriguing new structural and functional characteristics compared to other bothropic Lys49-PLA2s. We present in this article a comprehensive study with MjTX-I using several techniques, including crystallography, small angle X-ray scattering, analytical size-exclusion chromatography, dynamic light scattering, myographic studies, bioinformatics and molecular phylogenetic analyses.Based in all these experiments we demonstrated that MjTX-I is probably a unique Lys49-PLA2, which may adopt different oligomeric forms depending on the physical-chemical environment. Furthermore, we showed that its myotoxic activity is dramatically low compared to other Lys49-PLA2s, probably due to the novel oligomeric conformations and important mutations in the C-terminal region of the protein. The phylogenetic analysis also showed that this toxin is clearly distinct from other bothropic Lys49-PLA2s, in conformity with the peculiar oligomeric characteristics of MjTX-I and possible emergence of new functionalities inresponse to environmental changes and adaptation to new preys. © 2013 Salvador et al.
Keywords: MjTX I; oligomer; phospholipase A2; snake venom; unclassified drug; animal tissue; bioinformatics; Bothrops; bothrops moojeni; carboxy terminal sequence; controlled study; crystallography; dynamic light scattering; environment; gel permeation chromatography; male; molecular phylogeny; mouse; myography; myotoxic activity; nonhuman; physical chemistry; prey; protein conformation; protein structure; toxicity; X ray crystallography